Anatomy of Ag/Hafnia‐Based Selectors with 1010 Nonlinearity. Issue 11 (30th January 2017) - Midya, Rivu; Wang, Zhongrui; Zhang, Jiaming; Savel'ev, Sergey E.; Li, Can; Rao, Mingyi; Jang, Moon Hyung; Joshi, Saumil; Jiang, Hao; Lin, Peng; Norris, Kate; Ge, Ning; et al.
Abstract : A novel Ag/oxide‐based threshold switching device with attractive features including ≈10 10 nonlinearity is developed. High‐resolution transmission electron microscopic analysis of the nanoscale crosspoint device suggests that elongation of an Ag nanoparticle under voltage bias followed by spontaneous reformation of a more spherical shape after power off is responsible for the observed threshold switching.